(3LQGFe GdMGSHGJ GdBdjI ai GdJTQjY GdeUQi (B: s (3OQGSI ebGQfI (B/ s - (3GMeO eMehO eUWais; (3eMehO eMeO cHjT s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGhdJ gPg GdOQGSI LQGFe GdMGSHGJ GdBdjI ai GdJTQjY GdeUQi cOQGSI ebGQfI ef NdGd aUd JegjOi XGgQI LQGFe GdMGSH GdBdi hGdWHjYI GdNGUI HgG hbSejf NUU GdbSe GdChd GdfXQjI GdYGeI dLQGFe GdMGSH GdBdi hGdbSe GdKGfi dOQGSI LQGFe GdMGSHGJ GdBdjI hfNdU ef gPg GdOQGSI Gdi GdJhUjGJ GdBJjI GgejI GjLGO GdhSGFd GdefGSHI ddJYGhf GdOhdi ajeG jJYdb HLQGFe GdeYdheGJjI ef GLd GdJhajb Hjf GdJTQjYGJ GdNGUI HgPg GdLQGFe GgejI GaQGO fUhU NGUI JJYdb HCaYGd GdEJdGa hEYGbI GfXeI GdMGSHGJ hGdONhd hGdGYJQGV ZjQ GdeUQM Hg hGdGMJjGd GdeYdheGJis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B383-410s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjY GdeUQis; (3GdGehGd GdeYdheGJjIs; (3LQGFe GdMGSHGJ GdBdjIs; (3LQjeI GdGJdGas; (3LQjeI GdSQbIs; (3GdLQGFe GdeSJMOKI YHQ GdGfJQfJs; (3GdGOdI GdeSJNQLI ef GdGfJQfJs; (3GdNUhUjI GdeYdheGJjIs; (3LQjeI GdGMJjGd GdeYdheGJjs; (3XGgQI GdGLQGe GdeYdheGJjs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs